Commentary on the judgment of the Court of Justice of the European Union March 26, 2019, regarding the abusivity of certain clauses of advanced expiration of mortgage loans (from Modestino to Bauman, or from “solid law” to “liquid law”) - Díaz Fraile, Juan María (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The aim of this paper is to analyze the judgment of the CJEU of 26 of March of 2019. In this case, the CJEU ruled about the abusity of certaun clauses of advanced expiration of mortgage loans.